A study on the corrosion and mechanical properties of duplex coating Ti6Al4V/TiAlBN - Yusuf, Yusliza; Omar, Noor Irinah; Mohd Rosli, Zulkifli; Mohamad Juoi, Jariah (Taylor and Francis Ltd., 2016)
Titanium alloys, especially Ti6Al4V, have an excellent combination of properties. However, in many cases their application is limited because of poor wear and corrosion properties. In this research, a surface modification (duplex coating) has been carried out to improve the surface properties of Ti6Al4V. The duplex coating of the Ti6Al4V alloy was conducted with the aim of improving the corrosion resistance and mechanical properties of the alloy. In this study, plasma nitriding of Ti6Al4V was performed using a microwave plasma technique at a temperature 600°C for 1 and 3 h, followed by deposition of TiAlBN coating on plasma-nitrided samples for duplex coating purposes. Microstructural measurement revealed that the duplex coating process produces a relatively smooth and crack-free modified surface layer which is believed able to inhibit the occurrence of corrosion process. The electrochemical behaviour of duplex coating samples and untreated Ti6Al4V was evaluated using the Tafel Extrapolation method and it was found that the duplex coating significantly increased the corrosion protection property. In addition, the duplex surface obtained in this study has a superior surface hardness property compared to untreated Ti6Al4V, especially for samples with the longer nitriding time.